Larvicidal activity of Ferulago carduchorum Boiss. & Hausskn. against the main malaria vector, Anopheles stephensi - M. Khanavi; A. Baghernezhadian; F. GolFakhrabadi; M. R. Abai; H. Vatandoost; A. Hadjiakhoondi (Iranian Society of Pharmacognosy, 2016)
Background and objectives: Malaria is a remarkable cause of death in the world. Several ways are used by researchers to control or to decrease the detrimental effects of the disease, in which natural insecticides with less malaria vectors resistance and lower environmental damages are considered in last decades.The objective of this study was to assess the larvicidal activity of the whole flowering samples of Ferulago carduchorum Boiss. & Haussknagainst the main malaria vector Anopheles stephensi. Methods: The partition fractions of ethyl acetate, chloroform, methanol, and the total 80% methanol extract from Ferulago carduchorum were examined for larvicidal activity against late 3rd and early 4th instar larvae of malaria vector Anopheles stephensi. The LC50 and LC90 values were calculated by probit analysis. Results: The LC50 of the total extract, chloroform, ethyl acetate and methanol fractions were 0.4799, 0.2361, 0.7437 and 3.7017 ppm, respectively. The LC90 of the total extract, chloroform, ethyl acetate and methanol fractions were 1.5090, 0.4547, 1.8918 and 10.8857 ppm, respectively. Conclusion: On the basis of the presence of nonpolar compounds in the chloroform fraction, we can propose that the larvicidal activity of this fraction would be due to these compounds. The extract might be useful for improvement of new natural insecticides.